2021
DOI: 10.1126/sciadv.abg4302
|View full text |Cite
|
Sign up to set email alerts
|

Iron-sulfur cluster deficiency can be sensed by IRP2 and regulates iron homeostasis and sensitivity to ferroptosis independent of IRP1 and FBXL5

Abstract: Intracellular iron levels are strictly regulated to support homeostasis and avoid iron-mediated ROS production. Loss of iron-sulfur cluster (ISC) synthesis can increase iron loading and promote cell death by ferroptosis. Iron-responsive element-binding proteins IRP1 and IRP2 posttranscriptionally regulate iron homeostasis. IRP1 binding to target mRNAs is competitively regulated by ISC occupancy. However, IRP2 is principally thought to be regulated at the protein level via E3 ubiquitin ligase FBXL5–mediated deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…3H, S3B ). Intriguingly, shRNA knockdown of NFS1, a sulfur donor in ISC biogenesis, also induces IRP2 and TFRC and depletes FTH1, sensitizing cells to ferroptosis (effects on HIF were not investigated) reminiscent of that seen in our current study [65]. Since NFS1 contributes to the maturation of both cytosolic and mitochondrial Fe-S proteins (unlike ISCA1, ISCA2 and IBA57 that are believed to contribute only to mitochondrial [4Fe-4S] assembly), our findings suggest that ISCA2 may play an earlier role in ISC assembly than previously thought [44, 66].…”
Section: Discussionmentioning
confidence: 74%
“…3H, S3B ). Intriguingly, shRNA knockdown of NFS1, a sulfur donor in ISC biogenesis, also induces IRP2 and TFRC and depletes FTH1, sensitizing cells to ferroptosis (effects on HIF were not investigated) reminiscent of that seen in our current study [65]. Since NFS1 contributes to the maturation of both cytosolic and mitochondrial Fe-S proteins (unlike ISCA1, ISCA2 and IBA57 that are believed to contribute only to mitochondrial [4Fe-4S] assembly), our findings suggest that ISCA2 may play an earlier role in ISC assembly than previously thought [44, 66].…”
Section: Discussionmentioning
confidence: 74%
“…When ferroptosis occurs, the level of IREB2 mRNA increases and aggravates ferroptosis. Knockdown of IREB2 can reduce ferroptosis [ 11 , 20 ]. Therefore, ferroptosis in steatotic liver IRI is likely to be related to the abnormal expression of IREB2 .…”
Section: Resultsmentioning
confidence: 99%
“…When ferroptosis occurs, its mRNA expression increases and promotes the occurrence of ferroptosis. Knocking down IREB 2 can reduce the occurrence of ferroptosis [ 11 , 20 ]. Studies have shown that spinal cord injury in rats involves ferroptosis and is accompanied by an increase in Ireb2 mRNA [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISC are made up of iron and sulfur ions to form [1Fe-0S], [2Fe-2S], [3Fe-4S] and [4Fe-4S] clusters (6,119). Suppressing ISC synthesis can activate IRP2 and promote ferroptosis sensitivity (120); in line with this finding, insufficient ISC maintenance has been shown to robustly activate the iron-starvation response and trigger ferroptosis (121). Notably, inorganic sulfur is first produced from the cysteine by the cysteine desulfurase NFS1 and ISC is formed on the ISC assembly enzyme (ISCU) with the help of frataxin (FXN) (122),Which was indicated to be localized in the mitochondrial matrix and participated in the biosynthesis of ISC and FXN deficiency accelerates erastin-activated ferroptosis (123).…”
Section: Iron and Ferroptosismentioning
confidence: 99%